A comparative study of post-operative astigmatism in superior versus superotemporal scleral incisions in manual small incision cataract surgery in a tertiary care hospital - Hazra, Soumyadeep; Saha, Tapes Kanti (International Journal of Clinical and Experimental Ophthalmology, 2021)
Background: In developing countries, manual small incision cataract surgery is a better alternative and less expensive in comparison to phacoemulsification and thus the incision is an important factor causing high rates of postoperative astigmatism resulting into poor visual outcome. Thus, modifications to the site of the incision is needed to reduce the pre-existing astigmatism and also to prevent postoperative astigmatism. Modification to superotemporal incision relieves pre-existing astigmatism majorly due to its characteristic of neutralizing against-the-rule astigmatism, which is more prevalent among elderly population and thus improves the visual outcome. Aims: To study the incidence, amount and type of surgically induced astigmatism in superior and superotemporal scleral incision in manual SICS. Methodology: It is a randomized, comparative clinical study done on 100 patients attending the OPD of Ophthalmology at a tertiary care hospital, with senile cataract within a period of one year and underwent manual SICS. 50 of them chosen randomly for superior incision and rest 50 with superotemporal incision. MSICS with PCIOL implantation were performed through unsutured 6.5 mm scleral incision in all. Patients were examined post-operatively on 1st day, 7th day, 2nd week and 4th week and astigmatism was evaluated and compared in both groups. Results: It is seen that on postoperative follow up on 4th week, 77.78% of the patients with ATR astigmatism who underwent superior incision had increased astigmatism whereas, only 13.63% of the patients with ATR astigmatism who underwent supero-temporal incision, had increased astigmatism but 81.82% had decreased ATR astigmatism. However, 77.78% of the patients with preoperative WTR astigmatism who underwent supero-temporal incision, had increased astigmatism, whereas 44.45% of the patients with WTR astigmatism preoperatively, had increased astigmatism in contrast to 50% had decreased amount of astigmatism. It is also seen that the supero-temporal incision group had more number of patients (78%) with visual acuity better than 6/9 at 4th postoperative week than superior incision group (42%). Conclusion: This study concludes that superior incision cause more ATR astigmatism postoperatively whereas superotemporal incision causes lower magnitude of WTR astigmatism, which is advantageous for the elderly. Besides superotemporal incision provides better and early visual acuity postoperatively.